An Environment-Tolerant Ion-Conducting Double-Network Composite Hydrogel for High-Performance Flexible Electronic Devices - Wenchao Zhao; Haifeng Zhou; Wenkang Li; Manlin Chen; Min Zhou; Long Zhao (Nano-Micro Letters, 2024)
Highlights Novel double-network (DN) ion-conducting hydrogel (ICH) based on a poly(ionic liquid)/MXene/poly(vinyl alcohol) system (named PMP DN ICH) was synthesized using freeze–thawing and ionizing radiation technology. The PMP DN ICH possesses a multiple cross-linking mechanism and exhibits outstanding ionic conductivity (63.89 mS cm−1), excellent temperature resistance (−60–80 °C) and decent mechanical performance. The well-designed PMP DN ICH shows considerable potential in wearable sensing, energy storage, and energy harvesting.